Ruminant Nutrition: The Role of Agriculture by Products in Beef Cattle Production - Agus, Ali (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Increasing demand on food of animal origin including red meat in developing country is predicted doubled or even three fold in 2050, while the production especially that from ruminant legs well behind the projected human requirements. Feeding and nutrition have been reported to be the main constraint to ruminant production. In Indonesia, such as in other tropical countries, availability of feedstuffs is fluctuating during the year. Discussion on the available feeds is urgent in the face of rapidly depleting natural resources, climate change, urbanization, population pressure, decreasing land for crop production, and the increasing competition of arable land for food, feed and biofuel production. The efficiency of use of the available feed resources is very important and determinant for animal performance and productivity. The utilization of low quality feed mainly from crop residues as well as agricultural by products and other non-conventional feed resources has a common practiced. However, the different technologies are needed to maintain feed availability, improve feed quality and to optimize the nutrient utilization by the animal. This paper discuss briefly role of agricultural by products in beef cattle production. One may explore more comprehensive information concerned in this issue by accessing the papers and previous review papers as indicated in the references listed. Â Key Words: Agricultural by Products, Nutritive Quality, Beef Cattle